Measuring and testing the effectiveness of a spatial decision support system - Crossland; Wynne (Hawaii International Conference on System Sciences, 27th. Vol. 5: Biotechnology, 1994)
A laboratory experiment was used to investigate the effects on decision-maker performance of using geographic information system (GIS) technology as a spatial decision support system (SDSS). Volunteer subjects completed a site location task that required decisions to be made based upon spatially referenced information. Significant differences were found between task solutions developed by SDSS users and those developed by non-SDSS users. SDSS users experienced shorter solution times and fewer errors for both levels of task complexity. A hypothesized interaction of SDSS usage and problem complexity with respect to solution time was confirmed.< >